Comments on the ostracod species Neohornibrookella transoceanica (Teeter, 1975), and its broader generic significance - Warne, Mark T. (Zootaxa, 2018)
The concept of the thaerocytherid ostracod genus Neohornibrookella was established by Jellinek (1993) on valve and carapace specimens from Kenyan coastal waters, identified by him as belonging to the species Cythere lactea Brady, 1866. Thus, Jellinek (1993) nominated Cythere lactea as the type species for Neohornibrookella. However, he misidentified these Kenyan specimens, which are here interpreted to belong to the broadly distributed, thermophilic shallow marine species, Hermanites transoceanica Teeter, 1975. In accordance with Article 70.3 of the International Code of Zoological Nomenclature, 1999, either the species originally nominated as the type species (Cythere lactea Brady, 1866), or the species represented by the Kenyan specimens on which the genus was described (Hermanites transoceanica Teeter, 1975), may be accepted as the type species for Neohornibrookella Jellinek, 1993. In accordance with Article 70.3.2 of the International Code of Zoological Nomenclature, 1999 I choose Hermanites transoceanica Teeter, 1975 as the types species for Neohornibrookella Jellinek, 1993 because it conforms with the established concept of the carapace morphology for this genus, as per discussion below.